Biodegradation of pretreated pig bristles by Bacillus cereus B5esz - Łaba, Wojciech; Kopeć, Wiesław; Chorążyk, Dorota; Kancelista, Anna; Piegza, Michał; Malik, Kinga (International biodeterioration & biodegradation, 2015)
The keratinolytic bacterium Bacillus cereus B5esz was applied to the biodegradation of pig bristles using two methods: a 24-h enzymatic digestion with concentrated culture fluid and a 10-day degradation under specific culture conditions. Prior to the degradation experiments, the effects of thermo-chemical substrate pretreatments with various compounds at various concentrations were evaluated. The highest degree of biodegradation in the enzymatic reaction was obtained when the bristles were pretreated with 100 mM sulphite, which enabled the accumulation of 1.78 mg ml−1 soluble proteins and 237 μg ml−1 free amino acids at 24.7% substrate loss. Similarly, the same substrate pretreatment facilitated degradation in bacterial culture conditions, which resulted in the accumulation of over 8 mg ml−1 protein at 30.7% substrate loss. After enzymatic digestion, the hydrolysates were rich in branched chain amino acids (valine, isoleucine and leucine), which represented nearly 50% of the total amino acid content. Initial substrate pretreatment resulted in further increments in leucine, isoleucine, valine, methionine, tyrosine and glutamic acid. •Pig bristles were subject to degradation with concentrated keratinases of B. cereus and under culture conditions.•Variants of the initial thermo-chemical pretreatment of pig bristles were assessed.•The thermo-chemical pretreatment of bristles with 100 mM sulphite was sufficient to improve the biodegradation rate.•The amino acid composition of bristle hydrolysates depended on the biodegradation technique.